A statistical study about vaccines used against Covid-19 in Nineveh Governorat Iraq - Nayyef Mustafa, Khalidah (YCAB Publisher, 2024)
Background:A total of 518 individuals vaccinated with three different COVID-19 vaccines were included in this study. The majority received the Pfizer vaccine, which was associated with mild side effects, while others experienced more severe symptoms such as headache and fever. Objective:To evaluate the types of COVID-19 vaccines administered, the age distribution of vaccinated individuals, and the vaccines' efficiency and safety, assessed by two criteria: prevention of reinfection and reduction of side effects. Methods:A cross-sectional study was conducted using a structured questionnaire from June 2021 to January 2022. Data were collected through in-person interviews, verification of vaccine cards, and personal information, followed by statistical analysis of the gathered data. Results:The most vaccinated age group was 36–50 years. The distribution of vaccines administered included Pfizer (86.4%), AstraZeneca (8.5%), and Sinopharm (5.4%). Vaccine effectiveness, based on the absence of reinfection post-vaccination, was highest for Pfizer (90.1%), followed by AstraZeneca (86.4%) and Sinopharm (78.6%). Adherence to preventive and sterilization measures was observed among vaccinated individuals, with 31.3% adhering completely and 49.4% adhering partially. Conclusion:The vaccines studied included Pfizer, AstraZeneca, and Sinopharm. The most vaccinated age group was 36–50 years, while the least vaccinated group comprised individuals over 50 years. All vaccines demonstrated mild side effects, with Pfizer being the most effective, followed by AstraZeneca and Sinopharm. Keywords:COVID-19 vaccines; age groups; vaccine safety; adherence post-vaccination